CpG ODN D35 improves the response to abbreviated low-dose pentavalent antimonial treatment in non-human primate model of cutaneous leishmaniasis. - Seth G Thacker; Ian L McWilliams; Beatrice Bonnet; Lydia Halie; Serge Beaucage; Swaksha Rachuri; Ranadhir Dey; Robert Duncan; Farrokh Modabber; Stephen Robinson; Graeme Bilbe; Byron Arana; et al. (Public Library of Science (PLoS), 2020)
Cutaneous leishmaniasis (CL) affects the lives of 0.7-1 million people every year causing lesions that take months to heal. These lesions can result in disfiguring scars with psychological, social and economic consequences. Antimonials are the first line of therapy for CL, however the treatment is lengthy and linked to significant toxicities; further, its efficacy is variable and resistant parasites are emerging. Shorter or lower dose antimonial treatment regimens, which would decrease the risk of adverse events and improve patient compliance, have shown reduced efficacy and further increase the risk emergence of antimonial-resistant strains. The progression of lesions in CL is partly determined by the immune response it elicits, and previous studies showed that administration of immunomodulatory type D CpG ODNs, magnifies the immune response to Leishmania and reduces lesion severity in nonhuman primates (NHP) challenged with Leishmania major or Leishmania amazonensis. Here we explored whether the addition of a single dose of immunomodulating CpG ODN D35 augments the efficacy of a short-course, low-dose pentavalent antimonial treatment regimen. Results show that macaques treated with D35 plus 5mg/kg sodium stibogluconate (SbV) for 10 days had smaller lesions and reduced time to re-epithelization after infection with Leishmania major. No toxicities were evident during the studies, even at doses of D35 10 times higher than those used in treatment. Critically, pentavalent antimonial treatment did not modify the ability of D35 to induce type I IFNs. The findings support the efficacy of D35 as adjuvant therapy for shorter, low dose pentavalent antimonial treatment.